Pengaruh Struktur Modal Dan Struktur Kepemilikan Terhadap Profitabilitas Perusahaan Pembiayaan Leasing Yang Terdaftar Di BEI Tahun 2019-2021 - Putri Anjarsari; Indah Ariffianti; Baiq Desthania Prathama (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat (LP3M) Sekolah Tinggi Ilmu Ekonomi AMM (STIE AMM) Mataram, 2024)
This research aims to determine the influence of capital structure and ownership structure on the profitability of leasing finance companies listed on the Indonesia Stock Exchange in 2019-2021. This type of research is associative with a sampling technique using purposive sampling. The total sample is 13 companies and the number of observations is 39 companies. The analytical method used is multiple linear regression analysis. The results of the multiple linear regression analysis are Y = -32.564 + 0.405 X1 + 1.931 X2. Based on the research results, it shows that partially the capital structure variable (DER) with a significance value of 0.000<0.05 shows that it has a significant effect on profitability. On the other hand, partial ownership structure (INST) with a significance value of 0.571>0.05 has no significant effect on profitability. Simultaneously, capital structure (DER) and ownership structure (DER) with a significance value of 0.000<0.05 have a significant effect on profitability (ROE). Among the capital structure (DER) and ownership structure (INST) variables, the most dominant influence is the capital structure variable (X1) with a beta coefficient value of 0.737.